2016
DOI: 10.1080/15384047.2016.1235668
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of the Retinoblastoma protein (Rb) inhibits cancer cell EMT via Zeb

Abstract: The tumor suppressor Retinoblastoma (Rb) protein is highly phosphorylated in cancer cells largely due to the overexpression of cyclins or the loss of expression of cyclin dependent kinase inhibitors (cdki). Hyperphosphorylation of Rb promotes proliferation, and plays a role in the regulation of apoptosis. Recently, inhibition of cyclin dependent activity toward Rb has been identified as a strategy that has shown clinical efficacy. We utilized a method to induce phosphatase activity toward Rb in cells by shRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Zinc finger E-box-binding protein (ZEB) serves an important role in cell differentiation and embryonic development (7). It has been reported that ZEB is associated with biological processes, including tumor invasion and metastasis (8). Although embryo implantation into the endometrium is similar to the invasion mechanism of tumors, limited research has been conducted on ZEB in pernicious PP (9).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc finger E-box-binding protein (ZEB) serves an important role in cell differentiation and embryonic development (7). It has been reported that ZEB is associated with biological processes, including tumor invasion and metastasis (8). Although embryo implantation into the endometrium is similar to the invasion mechanism of tumors, limited research has been conducted on ZEB in pernicious PP (9).…”
Section: Introductionmentioning
confidence: 99%
“… 38 Dephosphorylation of the Rb, which leads to the activation of Rb, inhibits cancer cell EMT via Zeb. 39 The Rb also plays a pivotal role in the negative control of the cell cycle and in tumor progression. 40 Regarding the key role of p53-p21-Rb signaling in cell proliferation and mobility, we finally found that RNF126 promoted cell proliferation, drug resistance, and cell mobility in vitro via inhibiting p53/p21 in ubiquitin-dependent degradation.…”
Section: Discussionmentioning
confidence: 99%
“…24 In recent years, related studies have revealed that EMT is indispensable for tumor cell growth and survival. 25 In this study, we investigated the effects of carboplatin on the cytotoxicity of Rb cells through the lncRNA XIST/miR-200a-3p/NRP1 axis and found that carboplatin and micro-RNA-34a could inhibit EMT of Rb cells. The proliferation, invasion and ETM inhibition of Rb cells in carboplatin combined with siRNA-LncRNA XIST intervention group were stronger than those in carboplatin or siRNA-LncRNA XIST intervention group alone.…”
Section: Discussionmentioning
confidence: 99%